Felicitous Life with an Emphasis on Islamic Teachings - Hatami, Mohammadreza (Asian Journal of Islamic Psychology, 2024)
A felicitous life has always been the concern of the Islamic society and the present paper aims to explore the documents of Islamic teachings that refer to this issue. The research seems necessary to determine the basic dimensions of life to become operational. In this regard, the present paper tries to study Islamic teachings related to felicitous life and describe and examine its important dimensions using descriptive and analytical methods. By searching the two concepts of "life" and "felicity" in Islamic teachings, the materials related to the basic aspects of a felicitous life can be identified. Islamic texts (verses of the Holy Qur'an and narrations) that are mostly oriented to divinity and hereafter include descriptive and explanatory sentences about how to live. According to Islamic teachings, felicity consists of many components, each of which has a constructive contribution to a felicitous life. Life is a valuable capital and a hidden treasure, in which felicity and success depend on happiness, goodness, and worthiness. Happiness brings us bliss and joy in life; Goodness leads us to ethical living and altruism, and worthiness makes our life purposeful and meaningful. To live well or felicitously, one must learn "how to live" and deal with the important aspects of life.